Analisis Perbandingan Profitabilitas Produk Melalui Activity-Based Costing Dan Metode Tradisional: Systematic Literature Review - Ilham, Muhammad Ilham Rezki Wijaya; Riko, Mudriko Ahyulindo; Andhara, Andhara Az Zahra; Indri, Indri Natalia; Rifani, Rifani Akbar Sulbahri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The current business competition demands that all business actors be able to determine the total costs that the Company will incur to produce or even obtain goods or services that can be sold within a certain period. The process of determining production costs is a crucial factor because this process will affect the company's profitability. Calculation efforts using various accounting methods can be employed to determine the accurate calculation of production costs, such as the Traditional method and also the Activity-Based Costing (ABC) method. Although these two methods are often discussed, there is still limited research that systematically summarizes the comparison of these two methods, especially those reviewing aspects of effectiveness as well as the accuracy of overall production cost calculation. Therefore, through a Systematic Literature Review approach following the PRISMA protocol, this study aims to analyze the effectiveness of the Activity-Based Costing (ABC) method in providing more accurate cost information compared to traditional methods, as well as its impact on improving product profitability. The study results show that the ABC method is able to minimize cost distortions (undercosting and overcosting) by using cost drivers that align with activities, with one piece of literature noting an increase in cost calculation accuracy of up to 12–25%. The literature review results demonstrate that the accuracy of the Cost of Goods Manufactured (COGM) directly contributes to profitability through the determination of more competitive selling prices and more precise strategic decision-making for the company. These findings are expected to serve as a reference and guide in managing production costs more transparently and effectively to increase profits.